Factors Causing Time Delays Completion of Construction Projects (Case Study on Facilities Building Construction Project Sports Stage 5 Construction of The East Stand) - Arif, Al; Wibowo, Kartono; Sumirin, Sumirin; Ni'am, Moh. Faiqun (Journal of Green Science and Technology, 2024)
Inaccuracy in planning project activities during project implementation greatly affects implementation delays in the field. The purpose of the study is to determine and analyze: (1) the causal factors that contribute to project completion delays, (2) the causal factors that contribute to the dominant delay in project completion, and (3) delay risk management. In the Sports facilities (Eastern Tribune Development) project. Cirebon Regency. This study is a type of quantitative descriptive study. Data collection was done through FGD, interviews and questionnaires distributed to 10 qualified respondents in the construction sector. The resources of this study are the cause of the delay in the completion of the projects. A House of Risk (HOR) approach was used to analyze the data. Research results show that (1) Cirebon Regency Sports Facilities Building (Eastern Tribune Development) project has 14 risk events and 17 identified risk causes that cause delays. (2) Control factors that cause delays in project completion include: material factors, contract document factors, project owner factors, and contractor and design consultant factors, and (3) delay risk management options, including: (a) good communication and coordination. with the owner; (b) apply a comprehensive planning approach to procurement of materials, (c) coordinate current project drawings between consultants and field workers, (d) contact consultants and supervisors.